VR Paradise: Virtual Reality Based English Language Training Concept For Banyuwangi Tourism Awareness Group as an Effort to Create Superior HR Towards Era Society 5.0 - Nurotul Wafiroh; Afifah Nurliana; Deva Firdia (Pancaran Pendidikan, 2021)
VR Paradise is a Virtual Reality based English language Training concept aimed at Banyuwangi tourism awareness groups which includes several tour management groups, sellers at tourist sites, and tour guides at tourist attractions in the Banyuwangi area. The material contained in this training is tailored to the needs of the trainees. Training schedule is flexible and uses smartphone media so that it is easily accessed by trainees. The method of tracing ideas up to implementation is carried out by means of Research and Development by adopting 4 D model or The Four-D Model which consists of four stages namely define, design, develope, and disseminate. With the development of the concept of training the target is tourism awareness groups are expected to create superior human resources through the concept of education and training so that it can be used as an effort to empower people who are be able to improve the quality of tourism in the Banyuwangi area to ensure friendly service for local and foreign tourists towards the era of society 5.0